Assessing the feasibility of passive surveillance for maternal immunization safety utilizing archival medical records in Kinshasa, Democratic Republic of the Congo. Issue 26 (9th June 2022) - Gadoth, Adva; Mukadi Nkamba, Dalau; Arena, Patrick J.; Hoff, Nicole A.; Dzogang, Camille; Kampilu, David; Beya, Michael; Wong, Hui-Lee; Anderson, Steven A.; Kaba, Didine; Rimoin, Anne W.
Abstract: Introduction: Since the establishment of the Global Alignment of Immunization Safety Assessment in pregnancy (GAIA) case definitions in 2015, there has been an urgent need for field validation of pharmacovigilance feasibility in low- and middle-income countries. In this study, we assess the availability and quality of archival medical records at ten randomly selected high-traffic maternity wards in Kinshasa province, Democratic Republic of Congo (DRC). Methods: A retrospective cohort of mother-child pairs was established from all recorded births taking place at study sites between July 1, 2019 to February 28, 2020 through digitization of medical records. Adverse birth outcomes and maternal vaccination status, where available and linkable, were defined according to GAIA. Basic demographic information on mothers and newborns was also tabulated; birth outcomes were assessed for both intra-site prevalence and a pooled prevalence. Results: A total of 7, 697 mother-newborn pair records were extracted, with 37% of infants screening positive as cases of adverse outcomes. Maternal vaccination information was linkable to 67% of those cases. In total, 51% of stillbirths, 98% of preterm births, 100% of low birthweight infants, 90% of small for gestational age infants, 100% of microcephalic infants, and 0% of neonatal bloodstream infections were classifiable according to GAIA standards following initial screening. Forty percent of case mothers had some indication of tetanus vaccination prior to delivery in their medical records, but only 26% of case mothers met some level of GAIA definition for maternal vaccination during the pregnancy of interest. Conclusions: Archival birth records from delivery centers can be feasibly utilized to screen for stillbirth and maternal tetanus vaccination, and to accurately classify preterm birth, low birthweight, small for gestational age, and congenital microcephaly. Assessment of other neonatal outcomes were limited by inconsistent postpartum infant follow-up and records keeping.